2008
DOI: 10.1111/j.1467-9922.2008.00482.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Trait Emotional Intelligence and Sociobiographical Variables on Communicative Anxiety and Foreign Language Anxiety Among Adult Multilinguals: A Review and Empirical Investigation

Abstract: Dewaele, Jean-Marc; Petrides, and Furnham, Adrian (2008) The effects of trait emotional intelligence and sociobiographical variables on communicative anxiety and foreign language anxiety among adult multilinguals: A review and empirical investigation. Language Learning 58 (4) 911-960. This is an author-produced version of a paper published in Language Learning . This version has been peer-reviewed but does not include the final publisher proof corrections, published layout or pagination.All articles availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
321
10
8

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 370 publications
(375 citation statements)
references
References 82 publications
36
321
10
8
Order By: Relevance
“…Communicative anxiety has been found to be consistently lower in the first language compared to languages acquired later in life (Dewaele 2007c). This finding was confirmed by Dewaele et al (2008), where levels of communicative anxiety and foreign language speaking anxiety increased significantly from the L1 to the L2, and from the L3 to the L4 of multilinguals, across a range of situations. Levels of communicative anxiety were linked to a myriad of interacting psychological, situational, linguistic, cultural, and social factors.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…Communicative anxiety has been found to be consistently lower in the first language compared to languages acquired later in life (Dewaele 2007c). This finding was confirmed by Dewaele et al (2008), where levels of communicative anxiety and foreign language speaking anxiety increased significantly from the L1 to the L2, and from the L3 to the L4 of multilinguals, across a range of situations. Levels of communicative anxiety were linked to a myriad of interacting psychological, situational, linguistic, cultural, and social factors.…”
Section: Introductionsupporting
confidence: 72%
“…It is also the preferred language for expressing feelings or anger, for swearing, and also for performing cognitive operations like mental calculations (Dewaele 2004a(Dewaele , 2007a. Not surprisingly, participants suffered less from communicative anxiety in situations in their L1 than in a language acquired later in life (Dewaele 2007c;Dewaele et al 2008). In all these studies, selfperceived proficiency and the frequency of using the L2, L3, and L4 were strongly correlated with the dependent variables.…”
Section: Discussionmentioning
confidence: 68%
“…But this situation is contrary when one speaks a second language (Dewaele, 2006). Dewaele et al (2008) in his study for example show that foreign language anxiety has a significant negative effect on the recall of French L2 words. An anxious person would not necessarily suffer from anxiety when speaking a foreign language but a generally little anxious multilingual individual may suffer from foreign language anxiety when speaking a second language (Gardner & MacIntyre, 1994).…”
Section: B Definitionsmentioning
confidence: 91%
“…In the context of writing anxiety, no studies were found examining the relationship between EI and writing anxiety. Students reporting higher EI, however, report lower levels of language learning and communicative anxiety (Shao et al, 2013) and are more effective in managing their anxiety than students with lower EI (Dewaele, Petrides, & Furnham, 2008). We were therefore interested in examining the relationship between EI and writing anxiety in our study.…”
Section: Writing Anxiety Self-efficacy and Emotional Intelligencementioning
confidence: 99%